2013
DOI: 10.1155/2013/397382
|View full text |Cite
|
Sign up to set email alerts
|

Permanence in a Discrete Mutualism Model with Infinite Deviating Arguments and Feedback Controls

Abstract: We propose and deal with a discrete mutualism model with infinite deviating arguments and feedback controls. Sufficient conditions which guarantee the permanence of the system are obtained by using the difference inequality theory. The paper ends with brief conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Chen [11] argued that the general nonautonomous nonperiodic system is more appropriate, and he showed that the system (3) is permanent. For more work about cooperative system, we can refer to [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Chen [11] argued that the general nonautonomous nonperiodic system is more appropriate, and he showed that the system (3) is permanent. For more work about cooperative system, we can refer to [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%